Ground heat storage beneath salt-gradient solar ponds under constant heat demand. (1st February 2018) - Amigo, José; Suárez, Francisco
Abstract: Salt-gradient solar ponds are energy collectors and storage systems that provide continuous heat supply. Although many studies have investigated the thermal behavior of solar ponds, few researches have investigated how heat lost to the ground beneath a pond can be recovered. Here, a one-dimensional transient model is used to study the thermal interaction between a solar pond with constant heat demand and the ground beneath it. The ground thermal properties were dependent on temperature and moisture. As groundwater depth affects soil moisture distribution, higher thermal conductivities are observed when the groundwater table is shallow. Further, the mean temperatures at the bottom of the pond decrease exponentially as the groundwater depth is shallower. For deep groundwater tables, marginal variations in the groundwater table depth do not have a considerable impact on the pond's bottom temperatures. The addition of an insulation layer is only beneficial when the water table is shallow. When the water table is deep instead, the ground below the pond acts as an additional heat storage volume, permitting more stable temperatures in the pond throughout the year, making it more suitable for a constant heat demand. Highlights: Representation of the thermal dynamics in a solar pond and the ground beneath it. Algorithm for removing heat at a constant rate from a solar pond is proposed. Water dependent soil thermal properties are defined. Temperatures in a solar pond decrease exponentially as the water table is shallower. Insulating solar ponds exacerbate temperatures oscillations at the pond's bottom.